Comprehensive analysis of immunoglobulin expression in the mouse brain from embryonic to adult stages - Keiko Morimoto; Hitomi Sano; Michiko Takahashi; Rikuo Takahashi; Kazunori Nakajima (Journal of Neuroinflammation)
Abstract Immunoglobulin (Ig) is a critical molecule in the body’s defense against foreign substances such as bacteria and viruses. While traditionally considered B cell specific, studies have reported that Ig is also expressed by non-B cells. However, it is not known to what extent Ig is expressed in the brain and which type of variable regions are expressed. In this study, we elucidated the expression profile of Igs from embryonic to adult stages using single-cell RNA sequencing data and Ig repertoire analysis. Our results revealed that microglia express Ighm transcripts from embryonic to adult stages. These transcripts contain the upstream region of the Ighj region. In addition, Ighm is expressed in the layer 6 corticothalamic neurons, some of which co-express Ighg2c in the adult brain. In particular, we were able to generate a comprehensive profile of Ig variable region expression from embryonic to adult stages. Furthermore, the response of Ighm expression in microglia to lipopolysaccharide is markedly different from that in B cells, suggesting a novel, brain-specific role for the Ig gene, distinct from its classical function in the immune system.